An examination of culture and gender differences on the Love of Life Scale (LLS) and its psychometric properties - ʿAbd al-Khāliq, Aḥmad Muḥammad (Mental health, religion & culture, 2023)
The present research studied 2570 college students from seven countries: Egypt, Algeria, Kuwait, Lebanon, Iran, India and Turkey. The aims were: (a) to compare love of life mean scores between the seven samples, (b) to examine sex-related differences in love of life, and (c) to explore the principal components of the Love of Life Scale (LLS). The highest mean total LLS scores were for Kuwait, India, and Iran students, respectively. All countries differed significantly from one another, except Algeria versus Lebanon and India versus Iran. Higher mean LLS scores for women were found for each country. Cronbach alpha for the LLS was .93. A principal component analysis extracted from one to four components for individual countries, but one component was extracted for the total sample and labelled: Positive attitude towards life and Meaningfulness of life. The love of Life concept may be considered to be an important concept in positive psychology.